Nanostructural Control Enables Optimized Photoacoustic-Fluorescence-Magnetic Resonance Multimodal Imaging and Photothermal Therapy of Brain Tumor - Duan, Yukun (WILEY-V C H VERLAG GMBH, 2020)
10.1002/adfm.201907077